The social question in the twenty-first century : a global view - Breman, Jan; Harris, Kevan, 1978-; Lee, Ching Kwan; Linden, Marcel van der, 1952- (University of California Press, 2019)
"Want. Disease. Ignorance. Squalor. Idleness. Taken together, these comprise the 'giant evils' expressed in the Social Question--first raised in mid-nineteenth-century Europe to diagnose the crises produced by the emergence of the industrial society. Due to a globalized switch to neoliberalism in the final quarter of the twentieth century, the Social Question has made a worldwide comeback. The Social Question in the Twenty-First Century maps out the linked crises across regions and countries and identifies the renewed and intensified social question as a labor issue above all. The volume includes discussions from every corner of the globe, focusing on American exceptionalism, Chinese repression, Indian exclusion, South African colonialism, democratic transitions in Eastern Europe, and other phenomena. The effects of capitalism dominating the world, the impact of the scarcity of waged work, and the acknowledgment of how the dispossessed poor bear the brunt of the crisis are all evaluated in this carefully curated volume. Both thorough and thoughtful, the book serves as collective effort to revive and reposition the Social Question, reconstructing its meaning and its politics in the world today"--Provided by publisher.